Enhancing Preschoolers' Pre-Writing Skills Through Play-Based Image Media - Nadiyatus Sabila; Nadhirotul Laily (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
The preschool age period is known for significant improvements in various basic skills of children. The goal is to provide direct practical experience in a kindergarten setting, train students to integrate theoretical knowledge from lectures with practical skills in the field, and enhance both hard skills and soft skills. The research method used in this study can be described as an experimental approach with a quantitative design, aimed at testing the impact of using visual media on the pre-writing skills of preschool children. The use of visual media has proven effective in improving early childhood writing skills with positive impacts on fine motor and cognitive abilities, such as holding a pencil correctly, recognizing letter shapes, and writing more neatly. It also boosts children's motivation to learn and accelerates their understanding of writing concepts. The implication of this study suggests that visual media-based methods can serve as an effective strategy for accelerating the development of children's writing skills. Periode usia pra-sekolah dikenal dengan peningkatan signifikan pada berbagai kemampuan dasar anak. Tujuan untuk memberikan pengalaman praktis secara langsung di lingkungan TK, melatih mahasiswa memadukan pemahaman teoritis dari perkuliahan dengan keterampilan praktis di lapangan, serta meningkatkan hard skills dan soft skills individu. Metode penelitian yang digunakan dalam studi ini dapat dikatakan sebagai eksperimen dengan pendekatan kuantitatif, yang bertujuan untuk menguji pengaruh penggunaan media gambar terhadap kemampuan pra-menulis anak TK. Penggunaan media gambar efektif dalam meningkatkan keterampilan menulis anak usia dini dengan dampak positif terhadap kemampuan motorik halus dan kognitif, seperti memegang pensil dengan benar, mengenal bentuk huruf, dan menulis lebih rapi. Hal ini juga meningkatkan motivasi belajar anak-anak dan mempercepat pemahaman individu terhadap konsep menulis. Implikasi penelitian ini menunjukkan dapat dikatakan sebagai metode berbasis media visual dapat menjadi strategi efektif dalam mempercepat perkembangan keterampilan menulis anak.